1998
DOI: 10.1002/(sici)1097-4636(199802)39:2<229::aid-jbm9>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The fallacy of evaluating biomaterial wear-rates with water as lubricant: A hip simulator study of alumina-PTFE and CoCr-PTFE combinations

Abstract: Controversy surrounds wear data from hip-simulator studies, whether from the choice of lubricants or other parameters such as the particular biomaterial combinations used, and whether any such interactions could bias the resulting wear predictions. To investigate these phenomena, we studied the wear performance of CoCr and alumina femoral heads, in water and serum-based lubricants, using as our standard the polytetrafluoroethylene wear data derived clinically by Charnley. To model Charnley's clinical experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Waterlubricated tests of both materials showed wearrates much lower than the clinical rates (Saikko 1993, Clarke et al 1995, Good et al 1996, Phipatanakul et al 1998). All such in vitro studies maintained the high PTFE/PE wear ratio, as first described by Charnley. However, Charnley's PTFE revision cups showed that volumetric wear increased linearly with head-diameter (Charnley 1976).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Waterlubricated tests of both materials showed wearrates much lower than the clinical rates (Saikko 1993, Clarke et al 1995, Good et al 1996, Phipatanakul et al 1998). All such in vitro studies maintained the high PTFE/PE wear ratio, as first described by Charnley. However, Charnley's PTFE revision cups showed that volumetric wear increased linearly with head-diameter (Charnley 1976).…”
mentioning
confidence: 93%
“…The ball-size effect for both PTFE and PE has been duplicated in the laboratory with serum lubrication (Good et al 1996, Clarke et al 1997. However, in water-lubricated tests the wear-rates were 4 times lower than clinical and the ball-size effect was lost (Good et al 1996, Phipatanakul et al 1998.…”
mentioning
confidence: 99%
“…It is generally accepted that wear under these conditions is not realistic and the wear rates obtained are not directly applicable to artificial hip joints. The use of distilled water did not prevent the transfer film, formed on the ceramic counterface, while the use of more realistic protein containing bovine serum would prevent the formation of such a transfer film [29,30]. Wear under a more realistic multi-directional motion would be increased significantly, compared with the uniaxial motion considered [31,32].…”
Section: Discussionmentioning
confidence: 97%
“…40 – 42 The large joint literature indicates that use of nonphysiological lubricants, such as deionized water and saline, can lead to wear, which is highly unrepresentative of in vivo results. 40 , 43 45 Physiological based lubricants with protein concentrations similar to that found in human synovial fluid, coupled with appropriate load and motion inputs, have been shown to allow for close predictions of in vivo wear performance for total hip and knee replacements.…”
Section: Influential Wear Parametersmentioning
confidence: 99%